2004
DOI: 10.1186/1471-2407-4-48
|View full text |Cite
|
Sign up to set email alerts
|

Is drug-induced toxicity a good predictor of response to neo-adjuvant chemotherapy in patients with breast cancer? -A prospective clinical study

Abstract: Background: Neo-adjuvant chemotherapy is an integral part of multi-modality approach in the management of locally advanced breast cancer and it is vital to predict the response in order to tailor the regime for a patient. The common final pathway in the tumor cell death is believed to be apoptosis or programmed cell death and chemotherapeutic drugs like other DNA-damaging agents act on rapidly multiplying cells including both the tumor and the normal cells by following the same common final pathway. This could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 24 publications
3
31
0
Order By: Relevance
“…These results suggest that CYP1B1 does not directly inactivate docetaxel, but rather might promote cell survival in MCF-7 Txt cells, providing an explanation for its association with drug resistance. British Journal of Cancer (2008) Breast cancer affects a significant number of women worldwide and is a leading cause of cancer deaths (Chintamani et al, 2004). Current therapies for breast cancer include locoregional (surgical) treatment, anti-hormone therapy, radiotherapy and chemotherapy (O'Driscoll and Clynes, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that CYP1B1 does not directly inactivate docetaxel, but rather might promote cell survival in MCF-7 Txt cells, providing an explanation for its association with drug resistance. British Journal of Cancer (2008) Breast cancer affects a significant number of women worldwide and is a leading cause of cancer deaths (Chintamani et al, 2004). Current therapies for breast cancer include locoregional (surgical) treatment, anti-hormone therapy, radiotherapy and chemotherapy (O'Driscoll and Clynes, 2006).…”
mentioning
confidence: 99%
“…Breast cancer affects a significant number of women worldwide and is a leading cause of cancer deaths (Chintamani et al, 2004). Current therapies for breast cancer include locoregional (surgical) treatment, anti-hormone therapy, radiotherapy and chemotherapy (O'Driscoll and Clynes, 2006).…”
mentioning
confidence: 99%
“…It is also recommended to stay below the superior most IBN in order not to interfere with the lymphatic drainage of the upper extremity. Keeping dissection below the superior most IBN has been observed in various studies to be associated with lower incidence of upper limb lymphedema [4][5][6]. If one decides to sacrifice the intercostobrachial nerves, it is recommended that a cold knife rather than diathermy should be used to prevent postoperative neuralgia (Fig.…”
Section: Commandment-7-intercosto-brachial Nerves (Ibn)mentioning
confidence: 99%
“…This is primarily due to the fact that majority of breast cancers in the developing countries are locally advanced at presentation. These cancers may actually require some form of neoadjuvant chemotherapy to make them resectable [2][3][4]. This operation (MRM), however, is still the workhorse, and most surgeons must be trained to perform an optimum and oncologically safe MRM.…”
mentioning
confidence: 99%
“…Among patients with locally advanced breast cancer treated with neoadjuvant FAC regimen (5-fluorouracil, adriamycin, cyclophosphamide), Chintamani et al showed a significant positive correlation between the presence of vomiting (r = + 0.558), alopecia (r = + 0.802), and response to neoadjuvant chemotherapy. A significant negative correlation was observed between the absence of side effects and poor response to neoadjuvant chemotherapy [3]. The study of Ching-Hung et al was a retrospective study and GC use was not randomized but GCs were ordered by the physicians on an as-needed basis.…”
mentioning
confidence: 99%